Chen, C. J. (2006). The design, development and evaluation of a virtual reality based learning environment. - Chen, Chwen Jen (PKP Publishing Services Network, 2006)
Many researchers and instructional designers increasingly recognise the benefits of utilising three dimensional virtual reality (VR) technology in instruction. In general, there are two types of VR system, the immersive system and the non-immersive system. This article focuses on the latter system that merely uses the conventional personal computer setting. Although VR is recognised as an impressive learning tool, there are still many issues that need further investigations. These include (i) identifying the appropriate theories and/or models to guide its design and development, (ii) investigating how its attributes are able to support learning, finding out whether its use can improve the intended performance and understanding, and investigating ways to reach more effective learning when using this technology, and (iii) investigating its impact on learners with different aptitudes. This project chose a learning problem that was related to novice car driver instruction, to study some aspects of these issues. Indeed, the study provided valuable insights to a feasible instructional design theoretical framework, as well as an instructional development framework for VR based learning environments. In addition, it also developed understanding of the educational effectiveness of such a learning environment and its effect on learners with different aptitude.